The Vestiges of Childhood Interparental Conflict: Adolescent Sensitization to Recent Interparental Conflict. Issue 3 (27th August 2020) - Davies, Patrick T.; Thompson, Morgan J.; Martin, Meredith J.; Cummings, E. Mark
Abstract : This study examined whether childhood interparental conflict moderated the mediational pathway involving adolescent exposure to interparental conflict, their negative emotional reactivity to family conflict, and their psychological problems in a sample of 235 children ( M age  = 6 years). Significant moderated‐mediation findings indicated that the mediational path among Wave 4 interparental conflict during adolescence, change in youth negative reactivity (Waves 4–5), and their psychological problems (Waves 4–6) was significant for teens who experienced low, rather than high, levels of childhood interparental conflict (Waves 1–3). Supporting the stress sensitization model, analyses showed that adolescents exposed to high interparental conflict during childhood evidenced greater increases in negative reactivity than their peers when recent parental conflicts were mild.